Antioxidant and toxicity screening of Malaysian traditional herbs - Wong, Kristie Jo Yen (2015)
Malaysia is a biodiverse country rich in many herbs with desirable medicinal value and therapeutic properties. Therefore, the objective of the present study was to screen the antioxidant properties and toxicity effects of selected Malaysian traditional herbs. Eleven plant samples were selected based on their traditional uses and pharmacological properties. These plants were extracted using 80% methanol and screened for their antioxidant activities by both DPPH and FRAP antioxidant assays while the toxicity effects of the plant crude extracts were accessed using Zebrafish (Danio rerio) embryo and larvae toxicity assays. Results showed that three out of eleven plant crude extracts which were Melastoma malabathricum (leaf), Polygonum minus (leaf) and Ficus deltoidea (leaf) demonstrated high radical scavenging activities using DPPH assay with IC50 values of 120.17 ± 9.25 μg/mL, 118.57 ± 9.86 μg/mL and 267.53 ± 17.24 μg/mL, respectively. In addition, Melastoma malabathricum (leaf), Polygonum minus (leaf) and Ficus deltoidea (leaf) showed the highest total antioxidant activity using FRAP assay with IC50 values of 4.75 ± 0.12 μg/ml, 10.91 ± 1.42 μg/ml and 28.92 ± 1.54 μg/ml, respectively. Melastoma malabathricum (leaf), Polygonum minus (leaf) and Ficus deltoidea (leaf) showed moderate to slightly toxicity effects toward zebrafish embryo with LC50 values of 210.18 ± 27.36 μg/ml, 185.75 ± 7.84 μg/ml and 39.85 ± 1.73 μg/ml, respectively and LC50 values of 106.10 ± 3.54 μg/ml, 357.71 ± 27.96 μg/ml and 180.43 ± 30.22 μg/ml, respectively toward zebrafish larvae. Thus, our present results have shown that these three herbs might have the potential to be developed as herbal products to treat various oxidative based diseases due to their high antioxidant activities in vitro with moderate to slightly toxicity effects in vivo using zebrafish embryo model.